For Canada's sake: public religion, centennial celebrations, the re-making of Canada in the 1960s - Miedema, Gary R. (McGill-Queen's studies in the history of religion, 2005)
Public religion, public celebration, and the construction of nations : theoretical considerations -- "The things that we believe in in this country stand for Christianity" : Christian Canada to the 1960s -- An inclusive state, a servant church, and the waning of a Christian Canada -- The 1967 Centennial celebrations, the Canadian Interfaith Conference, and the building of an inclusive, pluralistic Canada -- Changing the meaning of the word "Canada" : state-sponsored public religion at Expo 67 -- "Should the government of Canada ... decide that all denominations must cooperate or unite before they can be present at Expo 67?" : negotiating a religious presence on the Expo isles -- The Christian Pavilion, the sermons from Science Pavilion, and the Pavilion of Judaism : varying constructions of public religion in 1967